Genotype-phenotype correlation in two Polish neonates with alveolar capillary dysplasia - Zuzanna Kozłowska; Zuzanna Owsiańska; Joanna P. Wroblewska; Apolonia Kałużna; Andrzej Marszałek; Yogen Singh; Bartłomiej Mroziński; Qian Liu; Justyna A. Karolak; Paweł Stankiewicz; Gail Deutsch; Marta Szymankiewicz-Bręborowicz; et al. (BMC, 2020)
Abstract Background Alveolar capillary dysplasia (ACD) is a rare cause of severe pulmonary hypertension and respiratory failure in neonates. The onset of ACD is usually preceded by a short asymptomatic period. The condition is refractory to all available therapies as it irreversibly affects development of the capillary bed in the lungs. The diagnosis of ACD is based on histopathological evaluation of lung biopsy or autopsy tissue or genetic testing of FOXF1 on chromosome 16q24.1. Here, we describe the first two Polish patients with ACD confirmed by histopathological and genetic examination. Case presentation The patients were term neonates with high Apgar scores in the first minutes of life. They both were diagnosed prenatally with heart defects. Additionally, the first patient presented with omphalocele. The neonate slightly deteriorated around 12th hour of life, but underwent surgical repair of omphalocele followed by mechanical ventilation. Due to further deterioration, therapy included inhaled nitric oxide (iNO), inotropes and surfactant administration. The second patient was treated with prostaglandin E1 since birth due to suspicion of aortic coarctation (CoA). After ruling out CoA in the 3rd day of life, infusion of prostaglandin E1 was discountinued and immediately patient's condition worsened. Subsequent treatment included re-administration of prostaglandin E1, iNO and mechanical ventilation. Both patients presented with transient improvement after application of iNO, but died despite maximized therapy. They were histopathologically diagnosed post-mortem with ACD. Array comparative genomic hybridization in patient one and patient two revealed copy-number variant (CNV) deletions, respectively, ~ 1.45 Mb in size involving FOXF1 and an ~ 0.7 Mb in size involving FOXF1 enhancer and leaving FOXF1 intact. Conclusions Both patients presented with a distinct course of ACD, extra-pulmonary manifestations and response to medications. Surgery and ceasing of prostaglandin E1 infusion should be considered as potential causes of this variability. We further highlight the necessity of thorough genetic testing and histopathological examination and propose immunostaining for CD31 and CD34 to facilitate the diagnostic process for better management of infants with ACD.